SUPERVISED INTERNSHIP IN THE TRAINING OF PHYSICAL EDUCATION TEACHERS: SCIENTIFIC PUBLICATIONS ON THE SUBJECT - Silvane Fensterseifer Isse; Vicente Molina Neto (Journal of Physical Education)
ABSTRACT The objective of this study was to analyze scientific publications that address the issue of supervised teaching in the training of Physical Education teachers. A systematic review was performed in databases in order to identify theses, dissertations and articles that deal with the subject. Two theses, seven dissertations and twenty-nine articles were identified. The results showed that the authors share the idea that supervised teaching plays a central role in teachers education. There is concern for the enhancement of the experiences of the trainee teachers. The study gave visibility to issues that need to be addressed: the limited dialogue between university and school; the role of the collaborator teacher and the basic school as preceptors; guidance to the trainee teachers by the educational institutions; the dichotomy between theory and practice and the privilege often given to utilitarian content activities.